Theranostics targeting fibroblast activation protein in the tumor stroma: 64Cu- and 225Ac-labeled FAPI-04 in pancreatic cancer xenograft mouse models - Watabe, Tadashi; Lindner, Thomas; Haberkorn, Uwe; Kratochwil, Clemens; Giesel, Frederik L. (Journal of nuclear medicine, 2020)
Fibroblast activation protein (FAP), which promotes tumor growth and progression, is overexpressed in cancer-associated fibroblasts of many human epithelial cancers. Because of its low expression in normal organs, FAP is an excellent target for theranostics. In this study, we used radionuclides with relatively long half-lives, 64Cu (half-life, 12.7 h) and 225Ac (half-life, 10 d), to label FAP inhibitors (FAPIs) in mice with human pancreatic cancer xenografts. Methods: Male nude mice (body weight, 22.5 ± 1.2 g) were subcutaneously injected with human pancreatic cancer cells (PANC-1, n = 12; MIA PaCa-2, n = 8). Tumor xenograft mice were investigated after the intravenous injection of 64Cu-FAPI-04 (7.21 ± 0.46 MBq) by dynamic and delayed PET scans (2.5 h after injection). Static scans 1 h after the injection of 68Ga-FAPI-04 (3.6 ± 1.4 MBq) were also acquired for comparisons using the same cohort of mice (n = 8). Immunohistochemical staining was performed to confirm FAP expression in tumor xenografts using an FAP-α-antibody. For radioligand therapy, 225Ac-FAPI-04 (34 kBq) was injected into PANC-1 xenograft mice (n = 6). Tumor size was monitored and compared with that of control mice (n = 6). Results: Dynamic imaging of 64Cu-FAPI-04 showed rapid clearance through the kidneys and slow washout from tumors. Delayed PET imaging of 64Cu-FAPI-04 showed mild uptake in tumors and relatively high uptake in the liver and intestine. Accumulation levels in the tumor or normal organs were significantly higher for 64Cu-FAPI-04 than for 68Ga-FAPI-04, except in the heart, and excretion in the urine was higher for 68Ga-FAPI-04 than for 64Cu-FAPI-04. Immunohistochemical staining revealed abundant FAP expression in the stroma of xenografts. 225Ac-FAPI-04 injection showed significant tumor growth suppression in the PANC-1 xenograft mice, compared with the control mice, without a significant change in body weight. Conclusion: This proof-of-concept study showed that 64Cu-FAPI-04 and 225Ac-FAPI-04 could be used in theranostics for the treatment of FAP-expressing pancreatic cancer. α-therapy targeting FAP in the cancer stroma is effective and will contribute to the development of a new treatment strategy.